Complementary belowground strategies underlie species coexistence in an early successional forest. Issue 2 (9th February 2023) - Yi, Ruojun; Liu, Qianyuan; Yang, Fengting; Dai, Xiaoqin; Meng, Shengwang; Fu, Xiaoli; Li, Shenggong; Kou, Liang; Wang, Huimin
Summary: Unravelling belowground strategies is critical for understanding species coexistence and successional dynamics; yet, our knowledge of nutrient acquisition strategies of forest species at different successional stages remains limited. We measured morphological (diameter, specific root length, and root tissue density), architectural (branching ratio), physiological (ammonium, nitrate, and glycine uptake rates) root traits, and mycorrhizal colonisation rates of eight coexisting woody species in an early successional plantation forest in subtropical China. By incorporating physiological uptake efficiency, we revealed a bi‐dimensional root economics space comprising of an 'amount‐efficiency' dimension represented by morphological and physiological traits, and a 'self‐symbiosis' dimension dominated by architectural and mycorrhizal traits. The early pioneer species relied on root–fungal symbiosis, developing densely branched roots with high mycorrhizal colonisation rates for foraging mobile soil nitrate. The late pioneer species invested in roots themselves and allocated effort towards improving uptake efficiency of less‐mobile ammonium. Within the root economics space, the covariation of axes with soil phosphorus availability also distinguished the strategy preference of the two successional groups. These results demonstrate the importance of incorporating physiological uptake efficiency into root economics space, and reveal a trade‐off between expanding soil physical space exploration and improving physiological uptake efficiency for successional species coexistence in forests.